The effect of sodium hyaluronate-chondroitin sulfate combined solution on cartilage formation in osteochondral defects of the rabbit knee: an experimental study - Tosun, Haci Bayram; Gurger, Murat; Gumustas, Seyit Ali; Uludag, Abuzer; Ucer, Ozlem; Serbest, Sancar; Celik, Suat (Dove Medical Press Ltd, 2017)
Objective: In focal cartilage lesions, multipotent mesenchymal stem cells in bone marrow are aimed to be moved into the defect area using subchondral drilling or microfracture method. However, repaired tissue insufficiently fills the defect area or cannot meet natural hyaline tissue functions, due to fibrous structure. We investigated the effect of a combined solution of sodium hyaluronate + chondroitin sulfate (HA+CS) administered intra-articularly after subchondral drilling on newly formed cartilage in rabbits with focal osteochondral defects. Materials and methods: A total of 32 New Zealand White mature rabbits, whose weights ranged from 2.5 to 3 kg, were randomly divided into four groups. Full-thickness osteochondral defect was formed in the left-knee medial femur condyles of all rabbits. Subchondral drilling was then performed. The following treatment protocol was administered intra-articularly on knee joints on days 7, 14, and 21 after surgery: group 1, 0.3 mL combined solution of HA+CS (20 mg CS combined with 16 mg HA/mL); group 2, 0.3 mL HA (16 mg/mL); group 3, 0.3 mL CS (20 mg/mL); and group 4 (control group), 0.3 mL saline solution. In the sixth week, all animals were killed and then evaluated histopathologically and biochemically. Results: There was significant articular cartilage formation in the HA+CS group compared to the HA, CS, and control groups. Hyaline cartilage formation was observed only in the HA+CS group. Cartilage-surface continuity and smoothness were significantly higher in the HA+CS and HA groups compared to the other groups. Normal cartilage mineralization was found to be significantly higher in the HA+CS group compared to the other groups. Increased levels of VEGFA and IL-1 beta in synovial fluid were observed in the HA+CS group. Conclusion: After subchondral drilling, intra-articular HA-CS combination therapy is a good choice to promote better quality new cartilage-tissue formation in the treatment of focal osteochondral defects.
Keywords: combined therapy; chondroitin sulfate; hyaluronate; osteochondral defect; subchondral drilling